2023
DOI: 10.1371/journal.pgph.0002141
|View full text |Cite
|
Sign up to set email alerts
|

Estimating excess mortality during the COVID-19 pandemic from a population-based infectious disease surveillance in two diverse populations in Kenya, March 2020-December 2021

Clifford Oduor,
Allan Audi,
Samwel Kiplangat
et al.

Abstract: Robust data on the impact of the COVID-19 pandemic on mortality in Africa are relatively scarce. Using data from two well-characterized populations in Kenya we aimed to estimate excess mortality during the COVID-19 pandemic period. The mortality data arise from an ongoing population-based infectious disease surveillance (PBIDS) platform, which has been operational since 2006 in rural western Kenya (Asembo, Siaya County) and an urban informal settlement (Kibera, Nairobi County), Kenya. PBIDS participants were r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 20 publications
0
1
0
Order By: Relevance
“…While VA algorithms for COVID-19 have been developed and performed well at predicting COVID-19 deaths [33], implementation of algorithms with a COVID-19-specific cause of death have been delayed [17]. Our findings indicated that simply relying on a respiratory underlying cause of death from a VA as a surrogate for COVID-19 deaths might underestimate the true burden, demonstrating the value of also measuring all-cause mortality during pandemics [34][35][36]. Furthermore, differences in antemortem and postmortem COVID-19 test results meant that antemortem positive COVID-19 test was not very sensitive for a positive COVID-19 test at death.…”
Section: Plos Global Public Healthmentioning
confidence: 96%
“…While VA algorithms for COVID-19 have been developed and performed well at predicting COVID-19 deaths [33], implementation of algorithms with a COVID-19-specific cause of death have been delayed [17]. Our findings indicated that simply relying on a respiratory underlying cause of death from a VA as a surrogate for COVID-19 deaths might underestimate the true burden, demonstrating the value of also measuring all-cause mortality during pandemics [34][35][36]. Furthermore, differences in antemortem and postmortem COVID-19 test results meant that antemortem positive COVID-19 test was not very sensitive for a positive COVID-19 test at death.…”
Section: Plos Global Public Healthmentioning
confidence: 96%